Dying online: live broadcasts of Chinese emerging adult suicides and crisis response behaviors - Jing Ma; Wei Zhang; Keith Harris; Qiang Chen; Xiaolin Xu (BMC, 2016)
Abstract Background Social media and online environments are becoming increasingly popular and integral to modern lives. The online presentation of suicidal behaviors is an example of the importance of communication technologies, and the need for professionals to respond to a changing world. These types of behaviors, however, have rarely been scientifically analyzed. This study aimed to examine the behaviors of both suicide broadcasters and their audience, with attention on prevention/crisis opportunities. Methods Multiple case studies were employed to explore live-broadcast suicide by Chinese emerging adults (aged 18-25 years). Six cases were selected (four males, two females; aged 19-24, M = 21.60, SD = 2.25), retrieved from 190 public documents (case range = 5 to 32; M = 11.50, SD = 10.37). A qualitative study based on grounded theory was adopted. Information on case background, stages, participants and their behaviors were collected. Results (1) Five stages of blogcast suicide incidents were revealed, including: Signaling, Initial reactions, Live blogcast of suicide attempts, Crisis responses, and Final outcomes. (2) Common behavioral trends (e.g., comforting, verbal abuse) were identified from the blogcast participants (e.g., active audience, peers, parents and police). (3) Suicide blogcasters exhibited tendencies to communicated signs of pain and cries for help. Conclusions This multi-case study found live presentations of suicidal behaviors offered unique opportunities to respond to suicidal crises, and also to learn more about the relationships between suicidal people and potential help sources. Findings showed many audience members wanted to be helpful but lacked appropriate skills or knowledge. Others engaged in suicide cyberbullying. The social media is an environment in the making. This study revealed that increasing knowledge and skills for crisis response and suicide prevention is needed. Such efforts could lead to empowered netizens and a more hospitable online world.